Developments in railway traffic engineering proceedings of a symposium held May 1967. (Institution of Civil Engineers, 1967)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium held on May 1967.